2016
DOI: 10.2142/biophysico.13.0_149
|View full text |Cite
|
Sign up to set email alerts
|

Importance of consensus region of multiple-ligand templates in a virtual screening method

Abstract: We discuss methods and ideas of virtual screening (VS) for drug discovery by examining the performance of VS-APPLE, a recently developed VS method, which extensively utilizes the tendency of single binding pockets to bind diversely different ligands, i.e. promiscuity of binding pockets. In VS-APPLE, multiple ligands bound to a pocket are spatially arranged by maximizing structural overlap of the protein while keeping their relative position and orientation with respect to the pocket surface, which are then com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Different ways of incorporating structural information have been proposed, for example by introducing spatial constraints targeting parts of the ligand that are common with a reference ligand, by guiding the placement of the ligand on reference atom-centered functions or electron density, or by scoring pose by 3D pharmacophore matching similarity [27,28,29]. Okuno et al suggested to combine multiple ligand-protein crystallographic structure into a reference grid [30,31]. The method, called VS-APPLE, aligned the ligand with the reference grid to predict the binding mode.…”
Section: Resultsmentioning
confidence: 99%
“…Different ways of incorporating structural information have been proposed, for example by introducing spatial constraints targeting parts of the ligand that are common with a reference ligand, by guiding the placement of the ligand on reference atom-centered functions or electron density, or by scoring pose by 3D pharmacophore matching similarity [27,28,29]. Okuno et al suggested to combine multiple ligand-protein crystallographic structure into a reference grid [30,31]. The method, called VS-APPLE, aligned the ligand with the reference grid to predict the binding mode.…”
Section: Resultsmentioning
confidence: 99%
“…In the process of seeking inhibitors of the target protein, an LBSV method, VS-APPLE 53,54 , was used. While conventional ligand-based VS methods adopt single ligand as a template, VS-APPLE adopts the multiple-ligand template, which is composed of multiple ligands bound to the same pocket, as a template.…”
Section: Methodsmentioning
confidence: 99%
“…Okuno et al . [ 10 ] discussed a new virtual screening method for drug discovery, especially in the case that a number of different ligands bind to a protein pocket. Even in the era of high performance computing, they warned that detailed understanding of the mechanisms of protein-ligand interactions is the prerequisite for the improvement of the screening.…”
mentioning
confidence: 99%